P99 Comparison Of Multiple Breath Washout Using A Commercial Device And A Mass Spectrometer In School Age Children With Cystic Fibrosis. (10th November 2014) - Duncan, JA; Raywood, E; Bush, A; Stocks, J; Aurora, P
Abstract : Background: Lung clearance index (LCI) measured by multiple breath washout (MBW) is a sensitive indicator of early lung disease in Cystic Fibrosis (CF). 1 MBW using sulphur hexafluoride (SF6 ) and mass spectrometry (MS) is currently the gold standard, but equipment is limited to a few centres. Although commercial devices based on SF6 have been developed, use of SF6 is expensive and restricted in some countries. Commercial devices using nitrogen (N2 ), which is cheaper and widely available, have been developed recently to increase accessibility of this test in research and clinical practice but have yet to be validated in children. The aim of this study was to compare values of LCI and Functional Residual Capacity (FRC) in children using the N2- MBW EasyOne Pro® LAB system (ndd Medical Technologies) and the MS (AMIS 2000, Innovision ApS). Methods: School-age children with CF and healthy controls completed MBW in triplicate on both the EasyOne Pro® and MS in random order on the same occasion. Within-subject agreement between devices for LCI and FRC was assessed by Bland-Altman analysis. Results: Of the 50 children recruited, all completed testing using MS, while 5 failed quality control on the EasyOne Pro® LAB. Paired results from both devices were obtained in 26 children with CF (mean age [range]) (13.3y[7.8y-17.4y]) and 19 controls (14.8y [12.5y-16.7y]). LCI was significantly higher in those with CF when using both devices (mean difference[95% CI], CF-controls): 2.47[1.4;3.5] for the MS-SF6 and 2.20[1.2–3.2] for N2 -MBW. There were no significant group differences between devices for either LCI (mean difference[95% CI]) -0.14[-0.45;0.16] or FRC -0.15L[-0.2;-0.08]. Within-subject variability was proportional to mean values (see Figure ) and ranged from 0.4–15.7% for LCI and 0.0–19.6% for FRC. Conclusion: Despite some previous reports that N2- washout results in higher LCI values than MS-SF6 washout, on average, we found similar values in both healthy school-age children and those with CF. Further work is required to examine causes of within-subject variability and assess validity and sensitivity over a wider age range, including preschool children, before commercial N2 -MBW devices can be confidently used in multi-centre trials. Reference: Aurora et al . Am J Respir Crit Care Med. 2011;183:752–8